Propagação vegetativa in vitro de Aniba rosaeodora Ducke (Lauraceae) - Jardim, Lyana Silva (2006)
Rosewood (Aniba rosaeodora Ducke), is a specie of great economic value for producing the essential oil linalol, used for perfume industry, causing intense exploration of the natural populations, and its disappearance in the areas of easy access. Like this, the purpose of this study was to establish a protocol for rosewood in vitro propagation, using apical and nodal segments and leaves, aiming at new techniques for specie’s reproduction. Firstly, the explants were submitted to differents process of disinfection, using solution of benomyl (4g.L-1), solution of sodium hipoclorite in 15% and 20%, with tween 20, in differents time exposure. After the explants were inoculated in MS medium, with 30g.L-1 of sucrose and 8g.L-1 of agar added to it , and they were left in dark conditions for 48 hours in B.O.D under 26ºC, and led to culture room. After, the apical and nodal segments, apparent healthy, were submitted to buds, roots and callus induction. They were transferred to culture medium containing growth regulators: BAP (0,0 e 4,0 mg.L -1), AIA, ANA and 2,4-D (0,0; 3,0 e 6,0 mg.L-1), and their respective combinations. The design was complete randomized in arranged factorial 9 X 2, with 18 treatments, each one with 15 replications. For the folial segments, were used: BAP, TDZ, ANA, AIA and 2,4-D (5,0 mg.L-1) to induction of foliar organogenesis. The design was randomized blocks consisted of 6 treatments, each one with 8 blocks e 2 replications. After 90 days, the plantlets took root in vitro were transplanted in plastic glass covered for transparent plastic sack, and evaluated in three kids of substratum for the acclimatization process. The first and the second substratum contained dark soil, clay and sand in proportions 2:1:1 and 1:2:1 (v/v) covered for vermiculite respectively; and the third substratum contained for vermiculite just. At the end of the study, the results indicated that the best process of disinfection for the apical and nodal segments was the use of benomyl solution (4g.L-1) during 24 hours, following the solution of sodium hipoclorite in 20% with tween 20, during 20 minutes, with 81,7% of survival of the explants. For the buds induction, the treatment containing 4,0 mg.L-1 of BAP + 6,0 mg.L-1 of AIA, showed the best, with the average of 1,50 buds/explant, followed by the treatment with 4,0 mg.L-1 of BAP + 6,0 mg.L-1 of ANA, which the average was 1,45 buds/explant. For the rooting induction, the best medium was containing 3,0 mg.L-1 of ANA, showing 1,68 roots/explant, followed by the treatment with 6,0 mg.L-1 of ANA, showing an 17 average of 1,39. For the callus induction, all the treatments formed callus, therefore, the medium containing 4,0 mg.L-1 of BAP + 6,0 mg.L-1 of 2,4-D, showed the best result, with 1,45 callus/explant, followed by the treatment with 4,0 mg.L-1 of BAP + 3,0 mg.L-1 of 2,4-D, of which an average was,1,40 callus/explant. For the folial segments, the best disinfection was the use of benomyl solution (4g.L-1) during 20 hours, followed by the solution of sodium hipoclorite in 20% with three drops of tween 20, during 15 minutes of exposure, showing 80% of survival of the explants. For the folial organogenesis, both treatments, F3 containg 5,0 mg.L-1 of ANA and F5 containg 5,0 mg.L-1 of 2,4-D, presented the best results for the callus induction, with an average of 1,4 callus/explant (both treatments). For the acclimatization process, none of the substratum presented efficiency for the plantlets adaptation in the new environmemtal conditions. The survival percentage of the explants for all the treatements was zero. In less of 30 days after the transplant, the plantlets presented complete necrose with partial lost of the leaves, and appearance of fungi in some replications. Key words: 1. Aniba rosaeodora Ducke; 2. In vitro propagation; 3. Growth regulators.